A method for strain analyses of surfaces with curved boundaries based on measured displacement fields. (2019) - Lehmann, Thomas; Stockmann, Martin; Ihlemann, Jörn
Abstract: This contribution deals with investigations of strain fields at the specimen surface. A notched cantilever beam made of epoxy was analyzed. In the notch-surrounding area inhomogeneous strain distributions with large gradients occur. For the detection of these strain fields, high-performance measuring methods and special evaluation methods are required. The detection of in-plane displacement fields was performed using Electronic Speckle Pattern Interferometry (ESPI). Based on B-spline approximation of the displacements, strains were determined. Besides a global evaluation, a parametrization of the notch-surrounding area was performed. The results show significant improvement compared to analyses without using the parametrization.